Torque-balancing algorithm for the redundantly actuated parallel mechanism. (April 2017) - Woo, Sang Hun; Kim, Sung Mok; Kim, Min Gun; Yi, Byung-Ju; Kim, Wheekuk
Abstract: In this work, a joint torque distribution algorithm of parallel mechanism (PM) with one redundant actuator is suggested. The algorithm is effective in avoiding the joint torque saturations. In the algorithm, the force equations are modified into the line equations representing the joint torque solutions. Then, the optimal joint torque distribution is found only by searching the intersections among the line equations. A comparative study of the suggested algorithm with the other typical actuator redundancy resolution algorithms, such as the minimum-norm (MN) torque algorithm, the weighted MN torque algorithm, and a task-priority algorithm, is conducted through simulations and experiments with a 3-DOF planar PM with one actuator redundancy. The simulations and experiments confirm that the suggested redundant actuation algorithm shows an enhanced performance in terms of joint torque limit avoidance and minimum output force/torque distortion over other preexisting algorithms.